QUALITY OF LIFE IN PATIENTS WITH GOUT - Gafforov Xudoyor Xudoyberdiyevich, Khusainova Munira Alisherovna, Toirov Doston Rustamovich, Kamolova Diyora Djamshedovna (Journals Park Publishing, 2023)
The aim is to identify factors associated with poor quality of life (QOL) in patients with gout.Material and methods. The study included 35 patients (31 men and 4 women) with a reliable diagnosis of gout. The average age of patients was 48.0±12.3 years, the median duration of the disease was 5.7 [3.0; 12.3] years, the number of arthritis attacks per year was 3 [1; 5], the average serum uric acid level (MC) was 510±120 mmol/l. 31.4% of patients took allopurinol, 40.5% had chronic arthritis, 36.5% — subcutaneous tofuses, 23% — coronary heart disease (CHD), 76% — arterial hypertension (AH), 15.4% — type 2 diabetes mellitus (DM), 10.2% — chronic kidney disease (CKD) with glomerular filtration rates <60 ml/min, 56% — obesity, 5.1% — chronic heart failure (CHF), 9.1% — a history of vascular catastrophes. To identify correlations between the indicators of QL according to the questionnaires EQ-5D, SF-36v1, functional status (FS) according to HAQ and clinical characteristics of the disease, as well as comorbid diseases, a correlation analysis according to Pearson and Spearman was carried out. Multiple regression analysis was used to identify factors that worsen QOL.
Keywords: gout, hyperlipidemia, uric acid, monaurate, quality of life; comorbid diseases.